The Relationship Between the Demonstration Method and Active Participation in 3 in 1 Junior Operator Custome Made Women Training - Arindha Sukma; Jamaris Jamna (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
This research was motivated by the high level of activity of the training participants in participating in the 3 in 1 Junior Operator Custome Made Women's training at the Padang Industrial Training Center, presumably because the instructor used the demonstration method in learning well. This research is quantitative with a correlational approach. The population in this study were all participants of the 3 in 1 Junior Operator Custome Made Women's Training at BDI Padang, totaling 45 people. While the sample was taken using the Simple Random Sampling technique, as many as 88% (40 people) because 12% of the population was used as a test instrument. The data collection technique used a questionnaire distributed via the google form link https://bit.ly/AngketPenelitianArindhaSukma. The data analysis technique used is the percentage formula and the product moment formula. The results of this study indicate that the training participants already have good learning activities, and there is a significant relationship between the demonstration method and the training participants' learning activities.